Full-Length Sequence Analysis of Chloroquine Resistance Transporter Gene in Plasmodium falciparum Isolates from Sabah, Malaysia - Lii Lian Tan; Tiek Ying Lau; William Timothy; Dhanaraj Prabakaran (The Scientific World Journal)
Chloroquine resistance (CQR) in falciparum malaria was identified to be associated with several mutations in the chloroquine resistance transporter gene (pfcrt) that encodes the transmembrane transporter in digestive vacuole membrane of the parasite. This study aimed to investigate the point mutations across the full-length pfcrt in Plasmodium falciparum isolates in Sabah, Malaysia. A total of 31 P. falciparum positive samples collected from Keningau, Kota Kinabalu, and Kudat, Sabah, were analyzed. pfcrt was PCR amplified and cloned prior to sequence analysis. This study showed that all the previously described 10 point mutations associated with CQR at codons 72, 74, 75, 76, 97, 220, 271, 326, 356, and 371 were found with different prevalence. Besides, two novel point mutations, I166V and H273N, were identified with 22.5% and 19.3%, respectively. Three haplotypes, namely, CVMNK (29%), CVIET (3.2%), and SVMNT (67.7%), were identified. High prevalence of SVMNT among P. falciparum isolates from Sabah showed that these isolates are closer to the P. falciparum isolates from Papua New Guinea rather than to the more proximal Southeast Asian CVIET haplotype. Full-length analysis of pfcrt showed that chloroquine resistant P. falciparum in Sabah is still prevalent despite the withdrawal of chloroquine usage since 1979.